The Effect of Vitamin C 1000 mg Beverages on Surface Roughness of Heat Cured Acrylic Resin - Almita Rifqi Destyarinta; Sri Wahyuningsih Rais; Martha Mozartha (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2020)
Introduction: Consumption of vitamin C 1000 mg beverages regularly can increased surface roughness of heat cured acrylic resin which caused by chemical reaction between acids in the beverages and heat cured acrylic resin. This caused by the acidic state in oral cavity and affect the surface roughness of heat cured acrylic resin. Objective: To determine the effect of vitamin C 1000 mg beverage on surface roughness of heat cured acrylic resin. Methods: Forty-four samples of heat cured acrylic resin sized 2 cm x 2 cm x 3 mm were divided into 4 groups. Samples were tested using surface roughness tester (Handysurf, Japan). Afterwards, group I immersed in You C1000 lemon, group II in You C1000 orange, group III in You C1000 apple, and control group in aquadest. Immersion was carried out for 3 days in a 37oC incubator with solutions replacement every 24 hours. Then, carried out the last measurement of surface roughness (post-test) of resin acrylic heat cured. Statistical test used in this study were paired t-test and one way ANOVA. Results: Paired t-test on group I, II and III showed that there were significant increase on surface roughness. One way ANOVA welch showed that there was asignificant difference. Post hoc Games-Howell showed that there was a significant difference on control group compared to group I, II and III. Conclusion: There was an effect of vitamin C 1000 mg beverage on surface roughness of heat cured acrylic resin